The art of phishing - Guarda, Teresa (2019)
Nowadays there are many threats that a company needs to protect itself. Everyone knows someone who has fallen for a coup by using an email, message or phone. People who pass by someone they trust, to extract data and money from the victim. These three ways are used to try convince someone to deliver accounts, credit card and document data in companies and at a particular level. According to Symantec, more than 6 hundreds of companies per day are targeted for Phishing, specifically Business E-Mail Compromise (BEC). In it, criminals pass through a central figure in the company, usually the CEO, and try to extract information or get employees to transfer money. This type of attack has generated in the last years losses of billions of dollars for the businesses affected. It is urgent that all company employees and individuals know as soon as possible what Phishing is and what steps to take.